A qualitative exploration of barriers to HIV prevention, treatment and support: Perspectives of transgender women and service providers. (25th November 2020) - Lacombe‐Duncan, Ashley; Kia, Hannah; Logie, Carmen H.; Todd, Kieran P.; Persad, Yasmeen; Leblanc, Gabrielle; Nation, Kelendria; Scheim, Ayden I.; Lyons, Tara; Horemans, Chavisa; Loutfy, Mona
Abstract: Transgender (trans) women experience barriers to access to HIV care, which result in their lower engagement in HIV prevention, treatment and support relative to cisgender people living with HIV. Studies of trans women's barriers to HIV care have predominantly focused on perspectives of trans women, while barriers are most often described at provider, organisation and/or systems levels. Comparing perspectives of trans women and service providers may promote a shared vision for achieving health equity. Thus, this qualitative study utilised focus groups and semi‐structured interviews conducted 2018–2019 to understand barriers and facilitators to HIV care from the perspectives of trans women ( n  = 26) and service providers ( n  = 10). Barriers endorsed by both groups included: (a) anticipated and enacted stigma and discrimination in the provision of direct care, (b) lack of provider knowledge of HIV care needs for trans women, (c) absence of trans‐specific services/organisations and (d) cisnormativity in sexual healthcare. Facilitators included: (a) provision of trans‐positive trauma‐informed care, (b) autonomy and choice for trans women in selecting sexual health services and (c) models for trans‐affirming systems change. Each theme had significant overlap, yet nuanced perspective, between trans women and service providers. Specific recommendations to improve HIV care access for trans women are discussed. These recommendations can be used by administrators and service providers alike to work collaboratively with trans women to reduce barriers and facilitators to HIV care and ultimately to achieve health equity for trans women.